Nicotinamide adenine dinucleotide biosynthesis promotes liver regeneration. Issue 2 (24th December 2016) - Mukherjee, Sarmistha; Chellappa, Karthikeyani; Moffitt, Andrea; Ndungu, Joan; Dellinger, Ryan W.; Davis, James G.; Agarwal, Beamon; Baur, Joseph A.
Abstract : The regenerative capacity of the liver is essential for recovery from surgical resection or injuries induced by trauma or toxins. During liver regeneration, the concentration of nicotinamide adenine dinucleotide (NAD) falls, at least in part due to metabolic competition for precursors. To test whether NAD availability restricts the rate of liver regeneration, we supplied nicotinamide riboside (NR), an NAD precursor, in the drinking water of mice subjected to partial hepatectomy. NR increased DNA synthesis, mitotic index, and mass restoration in the regenerating livers. Intriguingly, NR also ameliorated the steatosis that normally accompanies liver regeneration. To distinguish the role of hepatocyte NAD levels from any systemic effects of NR, we generated mice overexpressing nicotinamide phosphoribosyltransferase, a rate‐limiting enzyme for NAD synthesis, specifically in the liver. Nicotinamide phosphoribosyltransferase overexpressing mice were mildly hyperglycemic at baseline and, similar to mice treated with NR, exhibited enhanced liver regeneration and reduced steatosis following partial hepatectomy. Conversely, mice lacking nicotinamide phosphoribosyltransferase in hepatocytes exhibited impaired regenerative capacity that was completely rescued by administering NR. Conclusion : NAD availability is limiting during liver regeneration, and supplementation with precursors such as NR may be therapeutic in settings of acute liver injury. (Hepatology 2017;65:616‐630).